THE TRANSLATION STRATEGIES ANALYSIS ON NIGHT ATTHE MUSEUM MOVIE SUBTITLE:A case study of translation strategies in night at the museum movie subtitle - Dhanit Visesha, - (2008)
This research investigates subtitling strategies used in "The Night at the Museum" movie and analyzes theirs effect on the viewer. The researcher employed qualitative research design characterizing principles of descriptive method The researcher analyzed all dialogues using subtitling strategies of Gottlieb (In Taylor 2000). To find out the effect of the translation strategy to the viewer, the writer conducted interview and giving questionnaire. The findings of the research reveal that the subtitler uses nine strategies: transfer (39.25%) condensation (29.92%), paraphase (11.63%), deletion (7.92%), imitation (7.25%), decimation (1.18%), expansion (1.57%), resignation (1.04%) and transcription (0.19%). Transfer strategy is mostly used.